Tara tannin waste residue hydrogel film and preparation method and application thereof
Patent Information
- Application Number
- CN202610736214.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-05-26
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2046-05-26
AI Technical Summary
目前,塔拉单宁废渣大多作为废弃物填埋或焚烧处理,不仅造成生物质资源的浪费,还易引发环境污染问题
[0016]与现有技术相比,本申请的优点和积极效果在于:本申请以塔拉单宁废渣中的单宁酸为交联剂,充分利用废渣中的活性基团,与高分子形成多位点氢键复合物水凝胶膜,实现了工业废渣的高值化利用,减少了废弃物排放,同时大幅降低了水凝胶的生产成本,兼具经济与环境效益。
Smart Images

Figure CN122356534B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of hydrogel membrane technology, and more specifically, to a taratin waste hydrogel membrane, its preparation method, and its application. Background Technology
[0002] Hydrogels are polymeric materials with a three-dimensional network structure, possessing excellent water absorption, water retention, and biocompatibility, and have broad application prospects in fields such as heavy metal adsorption, drug sustained release, and tissue engineering. However, traditional synthetic polymeric hydrogels suffer from drawbacks such as low mechanical strength, limited adsorption capacity, poor biocompatibility, and high cost; while natural polymeric hydrogels, although biocompatibility is good, lack sufficient mechanical properties and stability, limiting their practical applications. Furthermore, cross-linking agents are required during the hydrogel preparation process.
[0003] Taratanine is a natural polyphenolic compound extracted from the pods of the tara bean, and it is widely used in the leather, food, and pharmaceutical industries. The industrial extraction process of taratanine generates a large amount of solid waste, known as taratanine waste residue, which mainly consists of cellulose, hemicellulose, lignin, and residual phenolic hydroxyl and carboxyl groups. Currently, most taratanine waste residue is disposed of through landfill or incineration, which not only wastes biomass resources but also easily leads to environmental pollution problems.
[0004] It should be noted that the information disclosed in the background section above is only used to enhance the understanding of the background of this disclosure, and therefore may include information that does not constitute prior art known to those skilled in the art. Summary of the Invention
[0005] The technical objective of this application is to address the above-mentioned shortcomings by providing a taratanin waste residue hydrogel membrane, its preparation method, and its application. This application uses tannic acid in the taratanin waste residue as a crosslinking agent, fully utilizing the active groups in the waste residue to form a multi-site hydrogen-bonded complex hydrogel membrane with polymers, thereby improving the mechanical strength and adsorption performance of the hydrogel membrane. Simultaneously, it provides a simple, green, and mild preparation method, as well as the application of this composite hydrogel in environmental remediation and biomedicine fields, realizing the high-value utilization of taratanin waste residue.
[0006] To achieve the above objectives, this application provides the following technical solution: According to one aspect of this application, a method for preparing a taratin waste residue hydrogel membrane is provided, comprising: S100, pretreating the taratin waste residue and modifying the pretreated taratin waste residue by an alkali activation method to obtain modified taratin waste residue; S200, preparing a matrix solution using a water-soluble polymer matrix and adding the modified taratin waste residue to the matrix solution, and obtaining a uniform mixture by ultrasonic dispersion and mechanical stirring; S300, pouring the mixture into a mold for spreading and allowing it to stand for 24-48 hours to obtain a taratin waste residue hydrogel membrane.
[0007] In some embodiments, in step S100, the activation temperature in the alkali activation method is 60-90℃, the activation time is 1-3h, and the alkali solution is a sodium hydroxide solution with a mass fraction of 5%-15%.
[0008] In some embodiments, in step S200, the water-soluble polymer matrix is one or more of polyethylene glycol, methylcellulose, polyvinyl alcohol, chitosan, polyacrylic acid, and alginate.
[0009] In some embodiments, the polyethylene glycol has a molecular weight of 100,000-150,000, and the methylcellulose has a viscosity of 400 mPa. s ~900 mPa The molecular weight of the polyvinyl alcohol is 120,000-200,000, the molecular weight of the chitosan is 100,000-310,000, the molecular weight of the polyacrylic acid is 150,000-300,000, and the molecular weight of the alginic acid is 50,000-200,000.
[0010] In some embodiments, step S100 includes: S110, taking taratanine waste residue, washing it with deionized water 3-5 times to remove soluble impurities, then vacuum drying it at 60-80°C to constant weight, mechanically pulverizing it and passing it through a 100-300 mesh sieve to obtain waste residue powder; S120, mixing the waste residue powder with alkaline solution at a mass ratio of 1:5-1:10, stirring and activating it at 60-90°C for 1-3 hours, filtering, washing until neutral, and drying to obtain modified taratanine waste residue.
[0011] In some embodiments, step S200 includes: S210, weighing the water-soluble polymer matrix by mass parts, adding it to deionized water and glycerol, stirring and dissolving it at 60-95°C until a uniform and transparent matrix solution is formed, and cooling it to room temperature; S220, adding the modified taratin waste residue obtained in step S100 to the matrix solution obtained in step S210, dispersing it ultrasonically for 20-40 minutes, and then mechanically stirring for 10-20 minutes to obtain a uniform mixture; wherein, the mass ratio of the water-soluble polymer matrix, the deionized water, the glycerol and the modified taratin waste residue is 40-75 parts: 100-140 parts: 5-10 parts: 5-20 parts.
[0012] According to another aspect of this application, a taratin waste hydrogel membrane is provided, which is prepared by the preparation method described above.
[0013] According to another aspect of this application, a hydrogel membrane prepared by the preparation method described herein or the application of the hydrogel membrane in heavy metal ion adsorption and dye wastewater treatment are provided.
[0014] In some embodiments, the heavy metal ion adsorption is for Pb 2+ Ions, Cd 2+ Ions, Cu 2+ ions or Cr 6+ Ion adsorption; the dye wastewater treatment involves the adsorption and removal of methylene blue, rhodamine B, or methyl orange dyes.
[0015] In some embodiments, the heavy metal ion adsorption is for Pb 2+ The dye wastewater treatment involves the adsorption and removal of methylene blue through ion adsorption.
[0016] Compared with the prior art, the advantages and positive effects of this application are as follows: This application uses tannic acid in taratanin waste residue as a crosslinking agent, makes full use of the active groups in the waste residue, and forms a multi-site hydrogen bond complex hydrogel film with polymers, realizing the high-value utilization of industrial waste residue, reducing waste emissions, and significantly reducing the production cost of hydrogel, thus achieving both economic and environmental benefits.
[0017] Furthermore, the preparation process of this application does not require high temperature and high pressure, the reaction conditions are mild and easy to control, the energy consumption is low, and there is no emission of toxic and harmful substances, which meets the requirements of green chemical production and is suitable for industrial-scale production.
[0018] Furthermore, the hydrogel membrane prepared in this application can be applied to multiple fields such as heavy metal adsorption and dye wastewater treatment, exhibiting diverse functions and strong practicality. Attached Figure Description
[0019] To more clearly illustrate the technical solutions in the embodiments of this application or the prior art, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0020] Figure 1 Photographs of the tartan tannin waste hydrogel membranes obtained in Examples 2-4 of this application are shown.
[0021] Figure 2 The infrared spectra of tartan dregs, polyacrylic acid, and the prepared tartan dregs hydrogel membrane are shown in Example 7 of this application.
[0022] Figure 3 Photographs of the mixtures prepared in Comparative Example 1 and Example 1 of this application are shown.
[0023] Figure 4 The Pb in Embodiment 1 and Comparative Example 2 of this application are shown. 2+ Adsorption curve.
[0024] Figure 5 The methylene blue adsorption rate curves of Example 1 and Comparative Example 2 of this application are shown. Detailed Implementation
[0025] To better understand the above-mentioned objectives, features, and advantages of this application, the application will be further described below with reference to the accompanying drawings and embodiments. It should be noted that, unless otherwise specified, the embodiments and features described in the embodiments of this application can be combined with each other.
[0026] The present application will be further described below with reference to the accompanying drawings and specific embodiments.
[0027] The raw materials used in the examples were all commercially available conventional products. The taratin waste residue was obtained from the extraction byproduct of a taratin production enterprise. The taratin waste residue contained 5-10% taratin by mass.
[0028] Example 1: A taratin waste residue hydrogel membrane is prepared from the following raw material components in parts by weight: 50 parts polyethylene glycol, 15 parts modified taratin waste residue, 130 parts deionized water, and 5 parts glycerin.
[0029] The preparation method is as follows: S100. Pre-treat the taratin waste residue and modify the pre-treated taratin waste residue using an alkali activation method, specifically including S110~S120: S110. Take taratin waste residue, wash it 4 times with deionized water, vacuum dry it at 70℃ to constant weight, pulverize it and pass it through a 200-mesh sieve to obtain waste residue powder. S120. The waste residue powder is mixed with a 10% sodium hydroxide solution at a solid-liquid ratio of 1:8, stirred and activated at 80°C for 2 hours, filtered, washed until neutral, and dried to obtain the modified taratin waste residue with a phenolic hydroxyl content of 10.2%. S200: A matrix solution is prepared using a water-soluble polymer matrix, and modified taratin waste residue is added to the matrix solution. A homogeneous mixture is obtained through ultrasonic dispersion and mechanical stirring; specifically, this includes S210~S220: S210. Weigh 50 parts of polyethylene glycol, add 130 parts of deionized water and 5 parts of glycerin, stir and dissolve at 90°C to form a uniform and transparent matrix solution, and cool to room temperature. S220. Add 15 parts of modified taratin waste residue to the matrix solution, ultrasonically disperse for 30 min, and mechanically stir for 15 min to obtain a homogeneous mixture. S300. Pour the mixture into a mold to spread it into a film, let it stand for 24 hours, and obtain the tartanin waste hydrogel film.
[0030] Example 2: A taratanin waste hydrogel membrane is prepared from the following raw material components in parts by weight: methylcellulose (400 mPa). The ingredients are 50 parts of s), 15 parts of modified taratin waste residue, 130 parts of deionized water, and 5 parts of glycerol. Other preparation methods are the same as in Example 1, and will not be repeated here.
[0031] Example 3: A taratanin waste hydrogel membrane is prepared from the following raw material components in parts by weight: methylcellulose (400 mPa). The ingredients were 60 parts of s), 10 parts of modified taratin waste residue, 122 parts of deionized water, and 8 parts of glycerol. Other preparation methods were the same as in Example 1, and will not be repeated here.
[0032] Example 4: A taratanin waste hydrogel membrane is prepared from the following raw material components in parts by weight: methylcellulose (400 mPa). The ingredients were 75 parts of s), 5 parts of modified taratin waste residue, 110 parts of deionized water, and 10 parts of glycerol. Other preparation methods were the same as in Example 1, and will not be repeated here.
[0033] Figure 1 Photographs of the taradamine waste hydrogel membranes (10 cm in diameter, 0.5 cm in thickness) obtained in Examples 2-4 of this application are shown. Figure 1As shown, the tartan dartane waste hydrogel membrane has good formation, and the color of the membrane gradually deepens with the increase of tartan dartane content.
[0034] Example 5: A taratanine waste residue hydrogel membrane is prepared from the following raw material components in parts by weight: 40 parts of chitosan with a weight average molecular weight of 200,000, 10 parts of modified taratanine waste residue, 140 parts of deionized water, and 10 parts of glycerol.
[0035] The preparation method is as follows: S100, activation temperature is 70℃, activation time is 3h, phenolic hydroxyl content is 9.5%, other steps are the same as in Example 1, and will not be repeated here.
[0036] S210. Weigh 40 parts of chitosan, add it to 140 parts of deionized water and 10 parts of glycerol, stir to dissolve at 70°C, and cool to room temperature.
[0037] S220. Add 10 parts of modified taratin waste residue to the matrix solution, ultrasonically disperse for 25 min, and mechanically stir for 20 min to obtain a homogeneous mixture.
[0038] S300. Pour the mixture into a mold to spread it into a film, let it stand for 48 hours, and obtain the tartanin waste hydrogel film.
[0039] Example 6: A taratanine waste residue hydrogel membrane is prepared from the following raw material components in parts by weight: 50 parts of alginic acid with a weight average molecular weight of 100,000, 20 parts of modified taratanine waste residue, 120 parts of deionized water, and 10 parts of glycerol.
[0040] The preparation method is as follows: S100, activation temperature is 90℃, activation time is 1h, phenolic hydroxyl content is 11.0%, other steps are the same as in Example 1, and will not be repeated here.
[0041] S210. Weigh 50 parts of alginic acid, add 120 parts of deionized water and 10 parts of glycerol, stir to dissolve at 60°C, and cool to room temperature.
[0042] S220. Add 20 parts of modified taratin waste residue to the matrix solution, ultrasonically disperse for 40 min, and mechanically stir for 10 min to obtain a uniform mixture.
[0043] S300. Pour the mixture into a mold to spread it into a film, let it stand for 36 hours, and obtain the taratin waste hydrogel film.
[0044] Example 7: A taratanine waste residue hydrogel membrane is prepared from the following raw material components in parts by weight: 50 parts of polyacrylic acid with a weight average molecular weight of 100,000, 20 parts of modified taratanine waste residue, 120 parts of deionized water, and 10 parts of glycerol. Other preparation methods are the same as in Example 1, and will not be repeated here.
[0045] Figure 2 The infrared spectra of tartan tannin waste residue, polyacrylic acid, and the prepared tartan tannin waste residue hydrogel membrane are shown in Example 7 of this application. Figure 2 As shown, comparing the infrared spectra (total reflectance infrared spectra) of the three, it can be clearly seen that the tartan tannin residue at 1204 cm⁻¹... -1 The strong absorption peak of CO stretching vibration in phenolic hydroxyl groups is observed in polyacrylic acid at 1204 cm⁻¹. -1 No absorption peak was observed, while the tartan tannin waste hydrogel membrane showed an absorption peak at 1204 cm⁻¹. -1 Not only does it contain a strong absorption peak of the CO stretching vibration in the phenolic hydroxyl group, but this peak also broadens and shifts to higher wavenumbers due to the formation of multiple hydrogen bonds with polyacrylic acid. This indicates that tartanine waste forms multiple hydrogen bonds with the polymer, thus allowing for the direct preparation of hydrogels without the need for additional crosslinking agents.
[0046] Comparative Example 1: Compared with Example 1, no taratanine residue was added, and the remaining components were prepared in the same way as in Example 1, to prepare a pure polyethylene glycol hydrogel membrane.
[0047] Comparative Example 1 could not be cured into a gel and remained an aqueous solution. Figure 3 The mixture prepared for Comparative Example 1 and Example 1 of this application, such as Figure 3 As shown, it is clear that Comparative Example 1 cannot solidify into a gel. When the centrifuge tube is tilted or inverted, the solution prepared in Comparative Example 1 can still flow and sink to the bottom, while the mixed solution prepared in Example 1 does not have fluidity even when inverted and has solidified into a hydrogel.
[0048] Comparative Example 2: Compared with Example 1, the taratin waste residue was not modified by alkali activation, and the remaining components were prepared in the same way as the preparation method to prepare the hydrogel membrane.
[0049] The hydrogel films of Examples 1, 5, 6 and Comparative Examples 1-2 were subjected to performance tests, including compressive strength and Pb. 2+ Adsorption capacity and methylene blue adsorption rate. The methods are as follows: Compression test: The test was conducted on a CMT6103 microcomputer-controlled electronic universal testing machine. The compression rate was 20 mm / min. The specimen was cylindrical with a height of 10 mm and a diameter of 12.5 mm.
[0050] Pb 2+ Adsorption capacity: Refer to HJ 786 The 2016 standard "Determination of Lead, Zinc and Cadmium in Solid Waste by Flame Atomic Absorption Spectrophotometry" shall be implemented.
[0051] 1. Prepare Pb solution with an initial concentration C0 of 200 mg / L. 2+ The standard solution was prepared by adjusting the pH of the solution to 5.5 ± 0.1 with 0.1 mol / L HCl.
[0052] 2. Accurately weigh 0.0500 g of the hydrogel membrane dried to constant weight (dry basis) and place it in a 100 mL Erlenmeyer flask.
[0053] 3. Add 50.0 mL of the above-mentioned Pb 2+ For the solution, place the conical flask in a 25°C constant temperature shaker and shake at 150 r / min for 24 h until adsorption equilibrium is reached.
[0054] 4. After shaking, filter the solution through a 0.22 μm microporous membrane and collect the filtrate.
[0055] 5. Pb in the filtrate was determined using a flame atomic absorption spectrophotometer at a wavelength of 283.3 nm. 2+ equilibrium concentration C e (mg / L).
[0056] Calculate Pb using the following formula 2+ Equilibrium adsorption capacity q e : q e = (C0- C) e )×V / m in: q e To balance the adsorption capacity (mg / g); C0 is Pb 2+ Initial concentration (mg / L); C e To determine the Pb content in the filtrate after adsorption equilibrium 2+ Concentration (mg / L); V is the solution volume (L, 0.050 L in this experiment); m is the dry weight of the hydrogel (g, 0.0500 g in this experiment).
[0057] Three parallel samples were made for each group of experiments.
[0058] Pb 2+ Determination of adsorption curves: Configure 13 groups with the same concentration of Pb 2+A 200 mg / L solution and an equal mass of hydrogel (0.05 g) were used. Then: at the end of the first hour, the concentration of the first group was measured → q1 was calculated; at the end of the second hour, the concentration of the second group was measured → q2 was calculated; the adsorption amounts were measured sequentially at 3, 4, 5, 6, 7, 8, 9, 10, 12, 18, and 24 hours. Three parallel samples were prepared for each experiment.
[0059] Methylene blue adsorption rate: Refer to HJ 1075 The 2019 standard for the determination of methylene blue in water, using a spectrophotometric method, shall be followed. Details are as follows: 1. Prepare a methylene blue standard solution with an initial concentration C0 of 100 mg / L and adjust the pH to 7.0 ± 0.2.
[0060] 2. Weigh 0.0500 g of hydrogel membrane sample and add 50.0 mL of methylene blue solution.
[0061] 3. Place the mixture in a 25°C constant temperature shaker and shake at 150 r / min for 120 min to reach adsorption equilibrium.
[0062] 4. After shaking, take the supernatant and filter it through a 0.22 μm filter membrane.
[0063] 5. Use ultraviolet light A visible spectrophotometer was used to measure the absorbance at 664 nm (the maximum absorption wavelength of methylene blue), and the equilibrium concentration Ce (mg / L) was obtained by conversion using a standard curve.
[0064] Calculate the methylene blue adsorption rate η using the following formula: η = (C0 - C e ) / C0×100% Where: η is the methylene blue adsorption rate (%); C0 is the initial concentration of methylene blue (mg / L); C e The residual concentration (mg / L) after adsorption equilibrium is given. Three parallel samples were prepared for each experiment.
[0065] Determination of methylene blue adsorption curve: Weigh 0.5000 g of hydrogel membrane sample and add 500.0 mL of methylene blue solution. Place the mixture in a 25℃ constant temperature shaker and shake at 150 r / min. At 0, 5, 10, 15, 20, 25, 30, 40, 50, 60, 80, 100, and 120 minutes, quickly pipette 5 mL of the solution (be careful not to remove the gel membrane; use a pipette tip with a filter). Immediately centrifuge the extracted solution (8000 rpm, 5 min), and collect the supernatant to avoid residual gel particles affecting absorbance. Measure the absorbance and calculate the adsorption rate at different times. Perform three replicates for each experiment.
[0066] The results are shown in the table below:
[0067] Figure 4 The Pb in Embodiment 1 and Comparative Example 2 of this application are shown. 2+ Adsorption curve. Figure 5 The methylene blue adsorption rate curves of Example 1 and Comparative Example 2 of this application are shown. Figure 4-5 As shown, the taratanin waste hydrogel membrane prepared in this application exhibits good mechanical strength and high heavy metal adsorption (Pb). 2+ The adsorption capacity and dye removal (methylene blue adsorption rate) are significantly better than the comparative example. Alkali activation treatment can further improve the performance of the hydrogel, verifying the effectiveness of the technical solution of this application.
[0068] Through the above specific embodiments, those skilled in the art can easily implement this application. However, it should be understood that this application is not limited to the specific embodiments described above. Based on the disclosed embodiments, those skilled in the art can arbitrarily combine different technical features to achieve different technical solutions.
Claims
1. A method for preparing a hydrogel membrane from taratanin waste residue, characterized in that, include: S100. The taratin waste residue is pretreated and modified by alkali activation method to obtain modified taratin waste residue. S200. A matrix solution is prepared using a water-soluble polymer matrix, and the modified taratin waste residue is added to the matrix solution. A uniform mixture is obtained by ultrasonic dispersion and mechanical stirring. S300: Pour the mixture into the mold and spread it without adding a chemical crosslinking agent. Let it stand for 24-48 hours to obtain a taratin waste hydrogel membrane. Step S200 includes: S210. Weigh the water-soluble polymer matrix according to the mass fraction, add it to deionized water and glycerol, stir and dissolve at 60-95℃ until a uniform and transparent matrix solution is formed, and cool to room temperature. S220. Add the modified taratin waste residue obtained in step S100 to the matrix solution obtained in step S210, disperse it ultrasonically for 20-40 minutes, and then stir mechanically for 10-20 minutes to obtain a uniform mixture; wherein, the mass ratio of the water-soluble polymer matrix, the deionized water, the glycerol and the modified taratin waste residue is 40-75 parts: 100-140 parts: 5-10 parts: 5-20 parts; In step S200, the water-soluble polymer matrix is one or more of polyethylene glycol, methylcellulose, polyvinyl alcohol, chitosan, polyacrylic acid, and alginate.
2. The method for preparing a taratin waste hydrogel membrane according to claim 1, characterized in that, In step S100, the activation temperature in the alkali activation method is 60-90℃, the activation time is 1-3h, and the alkali solution is a sodium hydroxide solution with a mass fraction of 5%-15%.
3. The method for preparing a taratanin waste hydrogel membrane according to claim 2, characterized in that, The polyethylene glycol has a molecular weight of 100,000-150,000, the methylcellulose has a viscosity of 400 mPa•s to 900 mPa•s, the polyvinyl alcohol has a molecular weight of 120,000-200,000, the chitosan has a molecular weight of 100,000-310,000, the polyacrylic acid has a molecular weight of 150,000-300,000, and the alginate has a molecular weight of 50,000-200,000.
4. The method for preparing a taratanin waste hydrogel membrane according to claim 2, characterized in that, Step S100 includes: S110. Take taratin waste residue, wash it with deionized water 3-5 times to remove soluble impurities, then vacuum dry it at 60-80℃ to constant weight, and then mechanically crush it and pass it through a 100-300 mesh sieve to obtain waste residue powder. S120. Mix the waste residue powder with alkaline solution at a mass ratio of 1:5-1:10, stir and activate at 60-90℃ for 1-3 hours, filter, wash until neutral, and dry to obtain the modified taratin waste residue.
5. A taratanin waste hydrogel membrane, characterized in that, Hydrogel membranes prepared by the preparation method according to any one of claims 1-4.
6. The application of the hydrogel membrane prepared by the preparation method according to any one of claims 1-4 or the hydrogel membrane according to claim 5 in the adsorption of heavy metal ions and the treatment of dye wastewater.
7. The application according to claim 6, characterized in that, The heavy metal ion adsorption is for Pb 2+ Ions, Cd 2+ Ions, Cu 2+ ions or Cr 6+ Ion adsorption; the dye wastewater treatment involves the adsorption and removal of methylene blue, rhodamine B, or methyl orange dyes.
8. The application according to claim 7, characterized in that, The heavy metal ion adsorption is for Pb 2+ The dye wastewater treatment involves the adsorption and removal of methylene blue through ion adsorption.
Citation Information
Patent Citations
Cellulose / tannin hydrogel and preparation method thereof
CN104262650A
Immobilized tannin for enriching rare scattered metal, preparation method and method for enriching rare scattered metal by using the immobilized tannin
CN111229175A